2021
DOI: 10.1177/0974910120974798
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interest Rate on Exchange Rate Within ASEAN Countries: Evidence from Linear and Nonlinear ARDL Frameworks

Abstract: This study examines the symmetric and/or asymmetric effects of changes in the interest rate on exchange rate of the ASEAN countries. It further aims to compare these linkages by using a dataset consisting of 48–68 quarterly data items, ranging over the period 2002–2017, of the ASEAN countries. Using both the linear autoregressive distributed lag (ARDL) and nonlinear ARDL (NARDL) approaches, the findings indicate that these effects vary from one country to another. We observe that changes in interest rates have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The situation will spark arbitrage activities as a result of profit arising from the disequilibrium price between countries. Ahmed and Mazlan (2021) update the finding of ASEAN countries by revealing that the effect of interest rate on the external purchasing power indicator varies with the existence of short run and long run asymmetries within ASEAN members. According to Phuc and Duc (2019), although inflation volatility, trade openness, and interest rate significantly influence changes of external purchasing power indicators in Australia, Japan, New Zealand and South Korea, the impact varies across the studied sample.…”
Section: Literature Reviewmentioning
confidence: 82%
“…The situation will spark arbitrage activities as a result of profit arising from the disequilibrium price between countries. Ahmed and Mazlan (2021) update the finding of ASEAN countries by revealing that the effect of interest rate on the external purchasing power indicator varies with the existence of short run and long run asymmetries within ASEAN members. According to Phuc and Duc (2019), although inflation volatility, trade openness, and interest rate significantly influence changes of external purchasing power indicators in Australia, Japan, New Zealand and South Korea, the impact varies across the studied sample.…”
Section: Literature Reviewmentioning
confidence: 82%
“…When interest rates appreciate, it increases the goods and services prices, decreases the local currency, and enhances the exchange rate volatility. Ahmed and Mazlan (2021) found that there is a short-run relationship between exchange rate and interest rate in ASEAN countries, and interest rate changes negatively affect the exchange rate. Tafa (2015) conducted a study on interest rate's association with the exchange rate.…”
Section: The Exchange Rate Impact On Interest Ratementioning
confidence: 99%
“…The strength of the country's currency is determined by how much it is exchanged. Therefore, it becomes pertinent to any economy desirous in achieving sustainable economic growth and development (Ahmed & Zarma, 1997). Exchange rate appreciation or depreciation mainly occur due to changes in demand and supply of currencies between countries, level of economic growth, prevailing trade balances, magnitude of country's foreign reserve, inflation levels, public debt profile, unemployment.…”
Section: Introductionmentioning
confidence: 99%